Comparaison des stratégies discursives d'étayage dans un conte et un récit d'expériences oraux - Rosat, Marie-Claude (My University, 1998)
This paper compares different strategies (questions, comments, reformulations, and repetitions) used by an adult in a situation of dialogue with language impaired and control preschool children. Two types of coproduction (a tale and a personal account) are analysed. The stability of the distribution of the various strategies in both situations of dialogue is the sign of the stability of the interaction. The plurifonctionality of these four strategies is the sign of a difference in managing the enunciative positions, according to the group of locutors and to their ages.